ANALISIS KESALAHAN DALAM PENULISAN KARANGAN NARATIF BAHASA INGGRIS OLEH SISWA KELAS XI SMK NEGERI 6 MANADO - Dehoop, Junike Lady (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
Abstrak This skripsi entitled â€œAnalisis Kesalahan dalam Penulisan Karangan Naratif Bahasa Inggris oleh Siswa SMK N 6 Manadoâ€, is an attempt to identify and analyze the types of errors in English grammar in narrative writings made by XI grade students of SMK N. 6 Manado. The data were taken from the studentsâ€™ writings. All data concerning grammatical errors were analyzed by using Ellisâ€™s theory. The method used in this research is descriptive. The results of this reserach show that there are three kinds of errors made by the students. First, omission is leaving out an item that is required for an utterance to be considered grammatical (8 types of omission found). Second, misinformation is using one grammatical form in placeÂ  of another grammatical form (10 types of misinformation found). And the last, misordering is putting the words in an utterance in the wrong order (5 types of misordering found). This researchÂ  is expected to contribute to the theory of error analysis especially in narative writings and to help students and readers to understand the error analysis in English narrative writings .